The evolutionally-conserved function of group B1 Sox family members confers the unique role of Sox2 in mouse ES cells. Issue 1 (December 2016) - Niwa, Hitoshi; Nakamura, Akira; Urata, Makoto; Shirae-Kurabayashi, Maki; Kuraku, Shigehiro; Russell, Steven; Ohtsuka, Satoshi
Abstract Background In mouse ES cells, the function of Sox2 is essential for the maintenance of pluripotency. Since the Sox-family of transcription factors are well conserved in the animal kingdom, addressing the evolutionary origin ofSox2 function in pluripotent stem cells is intriguing from the perspective of understanding the origin of pluripotency. Results Here we approach this question using a functional complementation assay in inducibleSox2 -null ES cells. Assaying mouse Sox proteins from different Groups, we found that only Group B1 and Group G proteins were able to support pluripotency. Interestingly, invertebrate homologs of mammalian Group B1 Sox proteins were able to replace the pluripotency-associated function of mouseSox2 . Moreover, the mouse ES cells rescued by theDrosophila SoxNeuro protein are able to contribute to chimeric embryos. Conclusions These data indicate that the function of mouseSox2 supporting pluripotency is based on an evolutionally conserved activity of the Group B1 Sox family. Since pluripotent stem cell population in developmental process could be regarded as the evolutional novelty in vertebrates, it could be regarded as a co-optional use of their evolutionally conserved function.